Mechanical Characterization of Unsaturated Loess and Numerical Simulation of Slope Stability Under Freeze–Thaw Cycles - Gang Wei; Jianyu Xiao; Yuanbing Xia; Weiheng Peng; Xinning Wu; Huijuan A; Huawen Qi; Zhilin Ren (Advances in Civil Engineering)
The soils in the eastern region of Qinghai, China, are characterized by typical unsaturated loess with poor engineering properties, rendering them susceptible to geological disasters such as landslides. To investigate the mechanical properties of these soils, triaxial and direct shear tests were conducted, followed by simulations of deformation and stability under freeze–thaw cycles using the discrete element software MatDEM, based on the experimental data. The findings indicate that (1) the stress–strain curves from both tests typically exhibit weak strain-softening behavior, with increased matric suction enhancing shear strength; (2) in the direct shear test, both cohesion (c) and the angle of internal friction (φ) rise with matric suction, whereas in the triaxial test, cohesion increases while φ decreases; and (3) an increase in freeze–thaw cycles results in a gradual decline in slope safety factor, though the rate of decline diminishes over time. Additionally, initial water content and slope gradient changes significantly affect slope stability. These insights are essential for geohazard risk assessment and the formulation of prevention and control strategies in Qinghai and similar alpine regions.